Latin America: liquid regionalism and contested regional authority - Nolte, Detlef (Frontiers in Political Science, 2025)
Latin American regionalism is in flux. Regional organizations and forums have experienced crises—some have become paralyzed, while others have disintegrated. Against this backdrop, the concept of liquid regionalism has gained traction. This article explores the analytical value of the concept, examining how it can be operationalized and applied to the current configuration of Latin American regionalism. While liquid regionalism captures important structural dynamics, it may overlook some of the potential advantages of institutional flexibility and the variable geometry of multilateral cooperation. The article proposes broadening the analytical lens by integrating research on regional authority and its contestation. Liquid regionalism and the contestation of regional authority highlight different but intersecting and complementary dimensions of the regional landscape. The ‘solidification’ of Latin American regionalism depends on the consolidation of regional authority. The article distinguishes between different forms of authority: hard authority, soft authority, and smart authority. While more solid forms of regionalism require hard authority, soft authority—grounded in the pooling of expertise—is more compatible with liquid regionalism and a technocratic turn in Latin American regional governance.